1997
DOI: 10.1021/om960817u
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Alkyl- and Aryl[hydrotris(pyrazolyl)borato]carbonylruthenium Complexes by Decarbonylation of Alcohols. Synthesis of TpRuH(H2)(PPh3) [Tp = Hydrotris(pyrazolyl)borate], an Observable Intermediate in the Decarbonylation Reaction

Abstract: Treatment of TpRuCl(PPh 3 )(CH 3 CN) (Tp ) hydrotris(pyrazolyl)borate) with NaBH 4 in ethanol did not yield the expected hydride complex TpRuH(PPh 3 )(CH 3 CN) (2) but rather the methyl carbonyl complex TpRu(CH 3 )(CO)(PPh 3 ) (1b). Formation of 1b was due to decarbonylation of ethanol by 2 generated in situ by NaBH 4 reduction of TpRuCl(PPh 3 )(CH 3 -CN). Analogous reactions in the presence of other primary alcohols RCH 2 OH (R ) H, C 2 H 5 , n-C 3 H 7 , C 6 H 5 , C 6 H 4 CH 3 -4, and C 6 H 4 Cl-4) led to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 54 publications
3
43
0
Order By: Relevance
“…Aryl methyl carbinols can be alkylated with many primary alcohols. The reactions with benzyl alcohols and heterocyclic alcohols (entries 2-7) give higher conversions than with primary aliphatic alcohols (entries [8][9][10][11][12]. The lowering of the conversion in alkylation reactions with primary alkyl alcohols is not attributable to selfcondensation of these alcohols because no self-condensation products were detected in the reactions; it is probably due to diminished electrophilicity of the carbonyl carbon atoms of the aldehydes generated via oxidation of the primary alkyl alcohols.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aryl methyl carbinols can be alkylated with many primary alcohols. The reactions with benzyl alcohols and heterocyclic alcohols (entries 2-7) give higher conversions than with primary aliphatic alcohols (entries [8][9][10][11][12]. The lowering of the conversion in alkylation reactions with primary alkyl alcohols is not attributable to selfcondensation of these alcohols because no self-condensation products were detected in the reactions; it is probably due to diminished electrophilicity of the carbonyl carbon atoms of the aldehydes generated via oxidation of the primary alkyl alcohols.…”
Section: Resultsmentioning
confidence: 99%
“…Formation of the phenyl carbonyl complexes M8 and M10 is probably due to benzaldehyde decarbonylation at the metal center. We have previously reported that the complex TpRu-A C H T U N G T R E N N U N G (PPh 3 )(CO)Ph (M10) can be prepared by reacting TpRuA C H T U N G T R E N N U N G (PPh 3 )A C H T U N G T R E N N U N G (CH 3 CN)H with benzaldehyde; [9] the Cp analogue M8 is independently prepared in this study. Decarbonylation of aldehydes by transition metal complexes to form carbonyl complexes is well-established.…”
mentioning
confidence: 99%
“…A doublet of doublets (J H,P ϭ 26.4, J C,H ϭ 9.3 Hz) is observed in the upfield region at δ ϭ Ϫ11.81 ppm, which can be assigned to the carbonyl hydride complex TpRu(PPh 3 )(CO)H (3), which we have previously reported. [7] The 31 P{ 1 H} spectrum exhibits a major singlet at δ ϭ 52.9 ppm, which is due to 2. A singlet at δ ϭ 66.1 ppm is assignable to 3, while the singlet at δ ϭ 30.9 ppm is identified as the signal of triphenylphosphane oxide, which was probably formed by CO 2 oxidation of PPh 3 .…”
Section: (B) Reaction Of 1 With Co 2 and H 2 In Methanol/thfmentioning
confidence: 99%
“…In our previous work, highpressure NMR spectroscopy monitoring of the catalytic CO 2 hydrogenation with 1 in hydrous THF revealed that the carbonyl hydride complex 3 was the major rutheniumcontaining species after prolonged heating at 100°C. Moreover, in the course of the reaction, a very small amount of TpRu(PPh 3 )(H 2 )H (4) [7] (4) with formic acid and the dihydrogen hydride species was present in such low concentration that it eluded detection by NMR spectroscopy. Examples relevant to the formation of 3 can be found in the literature.…”
Section: (B) Reaction Of 1 With Co 2 and H 2 In Methanol/thfmentioning
confidence: 99%
“…By contrast, a family of permethyl substituted complexes Cp * (R 3 P)RuH 3 (Cp * @C 5 Me 5 ) is well described [15], including the X-ray structure of Cp * (Ph 3 P)RuH 3 [16]. Complex 1a is a classical trihydride [16], whereas the isolobal tris(pyrazolyl)borate complex Tp(Ph 3 P)RuH(g 2 -H 2 ) exist in a hydride(dihydrogen) form [17], underpinning the strong effect of the ring on the extent of Ru-H interaction. Here, we report facile general access to a series of complexes Cp(R 3 P)RuH 3 (R 3 P@Ph 3 P (a), Ph 2 Pr i P (b), PhPr i 2 P (c) and Pr i 3 P (d)) and the crystal structure of complex Cp(Ph 2 Pr i P)RuH 3 .…”
Section: Introductionmentioning
confidence: 99%